2006
DOI: 10.1634/stemcells.2005-0303
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Induces Apoptosis in Primary Human CD34+ Hematopoietic Progenitor Cells

Abstract: STEM CELLS 2007;25:203-210

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 55 publications
3
25
0
2
Order By: Relevance
“…Although in some studies authors suggested a positive effect, [27][28][29][30][31][32][41][42][43][44] other studies suggested a negative effect. 45,46 Our findings show that Notch stimulates murine HSPCs over the short term but over longer periods depletes this population. Thus, the positive effects of supraphysiologic Notch signaling observed in earlier studies may have been produced through effects on differentiated multipotential precursors rather than LT-HSCs, which are rare and difficult to study via use of the earlier 4-color flow cytometric techniques.…”
Section: Discussionmentioning
confidence: 68%
“…Although in some studies authors suggested a positive effect, [27][28][29][30][31][32][41][42][43][44] other studies suggested a negative effect. 45,46 Our findings show that Notch stimulates murine HSPCs over the short term but over longer periods depletes this population. Thus, the positive effects of supraphysiologic Notch signaling observed in earlier studies may have been produced through effects on differentiated multipotential precursors rather than LT-HSCs, which are rare and difficult to study via use of the earlier 4-color flow cytometric techniques.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast to the murine studies, only a modest or no increase in the progenitor numbers was achieved by expressing activated Notch-1 in human CD34 + cord blood cells (Carlesso et al, 1999;Chadwick et al, 2007) or by incubation with Delta-1 (Jaleco et al, 2001), Delta-4 (Lauret et al, 2004) or Jagged-1 (Karanu et al, 2000;Karanu et al, 2001;Walker et al, 1999). This contrast with other reports showing that incubation of human cord blood cells with the immobilized Delta-1 combined with fibronectin fragments and cytokines induce a 100-fold increase in the number of CD34 + cells compare to controls (Ohishi et al, 2002) and a 16-fold increase in SCID Repopulating Cells (SRC) number compared to uncultured cells.…”
Section: Notch Signalingmentioning
confidence: 94%
“…In hematopoietic cells, Notch pathway plays either oncogenic or tumor suppressor roles, depending on the cell types [1][2][3]. In T cell acute lymphoblastic leukemia (T-ALL), Notch mutations are found in 50-70 % of patients [4].…”
Section: Introductionmentioning
confidence: 99%